Different spatiotemporal dynamics, ecological drivers and assembly processes of bacterial, archaeal and fungal communities in brackish-saline groundwater - Shufeng Liu; Qian Chen; Li, Jiarui; Li, Yanglei; Zhong, Sining; Hu, Jinyun; Cai, Hetong; Sun, Weiling; Ni, Jinren (Water ResearchWater Research, 2022)
The presence of brackish-saline groundwater (BSG) poses great harms for human health, agricultural and in-dustrial activity. Understanding how the major environmental features in BSG determine microbiota coalescence is crucial for groundwater monitoring optimization. Based on metabarcoding analysis of 242 PCR-amplified samples, we provided the first blueprints about distinct spatiotemporal distributions, ecological drivers and assembly processes of bacterial, archaeal and fungal communities in BSG obtained from new-constructed wells at Xiong'an New Area, China. Our study demonstrated that bacterial and archaeal communities exhibited signifi-cant spatial turnovers, while fungal community displayed the most obvious seasonal variation. Environmental filtering drove bacterial compositions more than those of archaea and fungi. Total dissolved solids (TDS), one of the most critical hydrochemical factors for salinization, had a stronger effect on bacterial spatiotemporal turn -over than on those of the other two taxonomic groups, while chemical oxygen demand (CODMn) was more significantly associated with prokaryotic community variations. Bacterial and archaeal taxa dominated the metacommunity network and connected closely, and TDS was mostly related to archaeal subnetwork topological features, suggesting a significant influence of TDS on species association patterns within archaea. Specific functional guilds like bacterial nitrite oxidation, anammox, and archaeal methanogenesis were enriched in lower-TDS habitats, while higher TDS favored bacterial communities involved in dark oxidation of sulfur compounds, fumarate respiration, and cellulolysis. Finally, we confirmed that bacterial and archaeal assembly processes were governed by determinism in each season, and that of fungi was more regulated by stochasticity. Higher TDS was speculated to lead bacterial assembly more deterministic and that of fungi more random. Together, these findings provided an integrate theoretical framework about the unique responses of the three life domains to brackish-saline stress, and had important implications for microbial ecological prediction in groundwater.